AJARAN EKAM SAT VIPRA BAHUDHA VADANTI SEBAGAI PARADIGMA BERINTERAKSI DALAM KEHIDUPAN MASYARAKAT MAJEMUK - Theresia Yashinta Tiara Lembong; Riedel Christian Gosal (PT. Giat Konseling Nusantara, 2026)
The teaching of Ekam Sat Vipra Bahudha Vadanti “Truth is one, though the wise call it by many names”offers a meaningful framework for interreligious engagement in diverse societies. Rather than treating other religions as theological systems to be judged or criticized, this study shows that they are understood as authentic and meaningful expressions of spirituality. Such an understanding resonates with John Hick’s view of a transcendent reality that is encountered and interpreted through different religious and cultural traditions. The pluralistic outlook that emerges from this reflection is not merely theoretical but grows out of lived philosophical reflection and everyday social experience. In this way, the findings contribute to and enrich Paul Knitter’s typology of interreligious relations. The religious life of the Hindu community at Pura Jagadhita Taas illustrates a distinctive and dynamic form of religious practice, marked by a high degree of fluidity. Here, religious communication is shaped less by rigid doctrinal claims and more by shared ethical values such as harmony, moral virtue, and respect for human dignity. Seen in this light, Ekam Sat functions not as an abstract theological formula, but as a lived spiritual orientation one that encourages inclusive social attitudes and strengthens cohesion within pluralistic communities.